2016
DOI: 10.1016/j.ymssp.2015.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty quantification in operational modal analysis with stochastic subspace identification: Validation and applications

Abstract: a b s t r a c tIdentified modal characteristics are often used as a basis for the calibration and validation of dynamic structural models, for structural control, for structural health monitoring, etc. It is therefore important to know their accuracy. In this article, a method for estimating the (co) variance of modal characteristics that are identified with the stochastic subspace identification method is validated for two civil engineering structures. The first structure is a damaged prestressed concrete bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
95
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(101 citation statements)
references
References 28 publications
4
95
0
2
Order By: Relevance
“…All data have been analysed via the Covariance-driven Stochastic Subspace Identification method (SSI/Cov), an Operational Modal Analysis (OMA) technique in the time-domain implemented in the MACEC code (Reynders et al, 2016). To this end, the data have been divided into one-hour long datasets.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…All data have been analysed via the Covariance-driven Stochastic Subspace Identification method (SSI/Cov), an Operational Modal Analysis (OMA) technique in the time-domain implemented in the MACEC code (Reynders et al, 2016). To this end, the data have been divided into one-hour long datasets.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…The assumptions on probability distributions of modal parameters come from the analysis of a set of data of the authors' personal experience as well as from a review of documented experimental cases found in scientific literature [29], [30].…”
Section: Numerical Study: Analyzing the Effects Of Motion Blur On Frfmentioning
confidence: 99%
“…As a result, the outcomes from such mathematical models may not be consistent with the clinical observations. Uncertainty is an unavoidable feature that affects prediction capabilities in real-world domains such as healthcare [9,10], manufacturing [11,12], signal processing [13,14], and etc. A certain amount of uncertainty is always involved in decision-making systems that do not encounter samples when the experimental data are insufficient to calibrate.…”
Section: Introductionmentioning
confidence: 99%